2016
DOI: 10.1007/s10457-016-9974-3
|View full text |Cite
|
Sign up to set email alerts
|

Provenance and pretreatment effect on seed germination of six provenances of Faidherbia albida (Delile) A. Chev

Abstract: A nursery experiment was conducted to determine the effects of seed pretreatment methods on the germination of Faidherbia albida at ICRAF, Nairobi from six provenances consisting of Awassa, Taveta, Lake Koka, Maseno, Chinzombo and Wagingombe. Seeds were subjected to five pretreatment methods namely nicking, soaking in acid, hot water, cold water and control. Germination percentages (GP), mean germination time (MGT) and germination index (GI) were calculated and the data was subjected to ANOVA. The study reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 15 publications
6
23
0
Order By: Relevance
“…Ahoton et al (2009) showed various tendencies on the seed germination rate and speed of Prosopis africana collected in Benin when submitted to four treatments having implied hot water, sulphuric acid, tap water and/or their combinations. Of these different works, germination rates of 90-100% were observed (Fredrick et al, 2016 in Faidherbia albida; Ahoton et al, 2009 in Prosopis africana; Moussa et al, 1998 in Hyphaenae thebaica; Njoukam, 1997 in Canarium schweinfurthii).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Ahoton et al (2009) showed various tendencies on the seed germination rate and speed of Prosopis africana collected in Benin when submitted to four treatments having implied hot water, sulphuric acid, tap water and/or their combinations. Of these different works, germination rates of 90-100% were observed (Fredrick et al, 2016 in Faidherbia albida; Ahoton et al, 2009 in Prosopis africana; Moussa et al, 1998 in Hyphaenae thebaica; Njoukam, 1997 in Canarium schweinfurthii).…”
Section: Discussionmentioning
confidence: 99%
“…These accessions (seeds) have been harvested in the localities of Dogbo (2013and 2016), and Tanguiéta (2014. The seeds of Dogbo constitute accessions Pop 16 and Sud 13, whereas those of Tanguiéta represent accession Nord 14, respectively.…”
Section: Plant Materialsmentioning
confidence: 99%
See 3 more Smart Citations